AB0962 LOW BACK PAIN AMONG MEDICAL STUDENTS: PREVALENCE AND RISK FACTORS. (13th June 2020) - Daldoul, C.; Boussaid, S.; Jemmali, S.; Rekik, S.; Sahli, H.; Cheour, E.; Elleuch, M.
Abstract : Background: Low back pain (LBP) is a common health problem among all age groups. Medical students do not seem to be spared. In fact LBP is one of the most common musculoskeletal disorder and its prevalence is variable ranging from 41% to 72%. Objectives: The aim of our study was to determine the prevalence of LBP among Tunisian medical students and to assess its associated factors. Methods: We conducted a cross-sectional study over 2 months carried out on medical students in a Tunisian medical college. A digital questionnaire entered by Google forms was sent by e-mail and was completed by the students. Our study included students from the first year of the first cycle of medical studies up to the third year of the second cycle. Socio-demographic, personal characteristics and life habits were collected. LBP was assessed using the Nordic musculoskeletal health questionnaire. The impact of low back pain was assessed using the Oswestry disability index (ODI). Results: One hundred and seventy-nine students were included. The mean age was 22.9 ± 2.3 years [19.64-38.21]. The sex ratio was 0.29. The average body mass index was 23.55 ± 4.22 kg / m2 [17.67-43.07]. 82% of the students were in the second cycle of medical studies. 26.4% of the students had a regular sports activity. 91.2% spent more than 4 hours a day in a sitting position. The point, annual, and lifetime prevalence of LBP among medical students was 41.2%, 80.4% and 90.6%, respectively. Low back pain was acute in more than 58.8%, subacute in 14.9% and chronic in 26.3%. The mean ODI score was 10.32% ± 8.48% [0-32%]. Students with LBP were significantly younger than students without LBP (p = 0.015). LBP was more common in students who spent more than 4 hours in a sitting position with a difference at the limit of significance (p = 0.059). Being in the 2nd cycle was significantly associated with the occurrence of LBP (p = 0.006). Poor screen projection in the amphitheater was significantly associated with the occurrence of LBP (p = 0.029).We found a statistically very significant relationship between the occurrence of LBP and the poor layout of the amphitheaters (p = 0.000). The feeling of depression was significantly higher among LBP students (p = 0.018). Feelings of fatigue, being overwhelmed, irritability and worry were more frequently found in LBP students, but this difference was not statistically significant. In a multivariate analysis, the only factors that remained statistically significant were feeling of depression (p = 0.046, OR = 3.88; CI = [1, 3-11, 55]) and the poor layout of the amphitheaters (p = 0.006, OR = 8.99; CI = [2.55-31.69]). Conclusion: The annual prevalence of LBP was 80.4%. These results testify to the magnitude of this health problem. The factors associated to LBP seemed to be essentially modifiable factors. This encourages special attention from medical schools to increase students' awareness of low back pain and to provide appropriate measures at reduce this musculoskeletal disorder. Disclosure of Interests: None declared